ÙØ¹Ø§Ù„ÙŠØ© ÙˆØ³Ø§Ø¦Ù„ Ø¨Ø·Ø§Ù‚Ø© Ø§Ù„ØµÙˆØ±Ø© Ø§Ù„Ø£Ø¨Ø¬Ø¯ÙŠØ© ÙÙŠ ØªØ±Ù‚ÙŠØ© Ø¥ØªÙ‚Ø§Ù† Ù…ÙØ±Ø§Ø¯Øª Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„ÙØµÙ„ Ø§Ù„Ø³Ø§Ø¨Ø¹ Ù…Ø¯Ø±Ø³Ø© Ù†Ù‡Ø¶Ø© Ø§Ù„ÙˆØ·Ù† ÙƒÙˆØªØ§Ø±Ø¬ Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© - Elsa Mayora; Nurul Aini; Moh Riadhi (Lughatu Ad-Dhat, 2023)
This research entitled The effectiveness of flashcard media Alphabet in improving mastery of Arabic vocabulary Class VII MTs NW Kotaraja. This research is classified as quantitative research with experimental research. In this research to find out about how the use of flashcard media Alphabet in improving the mastery of Arabic vocabulary students and the effectiveness of the use of flashcard media Alphabet in improving the mastery of Arabic vocabulary students. As for the results obtained after applying the method in accordance with the steps that have been made in the lesson plan, it is known that the alphabet flashcard media is effective in improving the mastery of Arabic vocabulary of Class VII Mts NW Kotaraja students. It can be seen from the calculation of T-test statistics show that there is an effectiveness of the use of flashcard media Alphabet to the mastery of Arabic vocabulary learners.